Pengaruh Pembelajaran Berbantuan Aplikasi Quizizz Terhadap Literasi Digital Siswa Kelas IV SDN Bilaporah 1 Bangkalan - Syafrilla Faigha Utami; Priyono Tri Febrianto (Jurnal Motivasi Pendidikan dan Bahasa, 2023)
The purpose of this study was to explain whether or not there was an effect of using the quizizz application on digital literacy of fourth grade students at SDN Bilaporah 1 Bangkalan. This type of research is experimental research with a quantitative approach. This study uses a posttest-only control design model. The research sample used in this study was fourth grade students at SDN Bilaporah 1 Bangkalan. The sampling technique used in this research is saturated sampling technique. Data was collected using performance test sheets. The results of data analysis calculated using the independent sample t-test show that the sig value is 0.000 where the value is less than 0.05. So these results indicate that there is an influence between quizizz application assisted learning on students' digital literacy in class IV SDN Bilaporah 1 Bangkalan.